Programmer's Companion to Algorithm Analysis, A - Leiss, Ernst (CRC Press, 2009)
Until now, no other book examined the gap between the theory of algorithms and the production of software programs. Focusing on practical issues, A Programmer's Companion to Algorithm Analysis carefully details the transition from the design and analysis of an algorithm to the resulting software program.